Coffee and Conflict in Colombia, 1886-1910 - Bergquist, Charles W. (Book collections on Project MUSE., 1986)
The appearance of Coffee and Conflict in Colombia, 1886-1910, had several important consequences for the entire field of Latin American history, as well as for the study of Colombia. Through Bergquist's analysis of this transitional period in terms of what has been called the dependency theory, he has left his mark on all subsequent studies in Latin American affairs; questions of economic development and political alignment cannot be dealt with without confronting Bergquist's work. he has also provided a major contribution to Colombian history by his examination of the growth of.